(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Interventions designed with families in mind were the primary focus of the research for older people and their caretakers. The information functional well-being problems on the part of the elderly and their caretakers were tested. The researcher used that comprised the FFNI sessions that focused on the family, exercises for balance and strength, changes that could be made to the home setting, sleep hygiene, and breathing exercises.